Extracellular Vesicles of the Hyperthermophilic Archaeon “Thermococcus onnurineus” NA1(T) - Choi, Dong Hee (Appl Environ Microbiol, 2015)
Extracellular vesicles (EVs) produced by a sulfur-reducing, hyperthermophilic archaeon, “Thermococcus onnurineus” NA1(T), were purified and characterized. A maximum of four EV bands, showing buoyant densities between 1.1899 and 1.2828 g cm(−3), were observed after CsCl ultracentrifugation. The two major EV bands, B (buoyant density at 25°C [ρ(25)] = 1.2434 g cm(−3)) and C (ρ(25) = 1.2648 g cm(−3)), were separately purified and counted using a qNano particle analyzer. These EVs, showing different buoyant densities, were identically spherical in shape, and their sizes varied from 80 to 210 nm in diameter, with 120- and 190-nm sizes predominant. The average size of DNA packaged into EVs was about 14 kb. The DNA of the EVs in band C was sequenced and assembled. Mapping of the T. onnurineus NA1(T) EV (ToEV) DNA sequences onto the reference genome of the parent archaeon revealed that most genes of T. onnurineus NA1(T) were packaged into EVs, except for an ∼9.4-kb region from TON_0536 to TON_0544. The absence of this specific region of the genome in the EVs was confirmed from band B of the same culture and from bands B and C purified from a different batch culture. The presence of the 3′-terminal sequence and the absence of the 5′-terminal sequence of TON_0536 were repeatedly confirmed. On the basis of these results, we hypothesize that the unpackaged part of the T. onnurineus NA1(T) genome might be related to the process that delivers DNA into ToEVs and/or the mechanism generating the ToEVs themselves.